Method of priming plants against abiotic stress factors - (:unkn) unknown (United States Patent and Trademark Office, 2017)
A method of reducing cellular damage to a plant by treating the plant with a compound containing an NO-releasing moiety and an H.sub.2S-releasing moiety covalently bonded to an aspirin derived core or a NOSH compound is claimed. The compounds may also be used in a method of priming a plant against abiotic stress factors and a method of promoting plant growth.
Keywords: Abiotic stress; Priming agents; Reducing cellular damage